Investigating factors influencing class attendance and performance of first-year Economics students - Swanepoel, C.; Beukes, R.; Yu, D. (South African Journal of Higher Education, 2021)
The academic success of first-year Economics students has been examined in many South African studies in Economic Education. These studies controlled for differences in demographic characteristics, last school examination (Matric) subjects and results, as well as lecture and tutorial attendance when investigating differences in students’ performance. While there is an abundance of international studies investigating the main reasons for attendance or non-attendance, these studies are rare in the South African context, especially in the field of Economics. Hence, this study fills the existing local research gap by investigating factors influencing lecture attendance as well as their possible impact on the performance of first-year Microeconomics students at the University of the Western Cape. The key empirical findings suggest that both lecture and tutorial attendance had a positive and significant impact on both the likelihood of qualifying to write the examination as well as the examination mark. In addition, students who enrolled in Economics in Matric and obtained better marks in first-year Macroeconomics in the previous semester performed significantly better in the Microeconomics examination. It was also found that the main reasons for not attending lectures are academically related, with the top reason being “busy studying for tests”. Furthermore, students who regarded tutorials as a replacement for lectures significantly suffered nearly five marks lower in the examination. We recommend revisions to teaching methods and making lecture attendance compulsory and part of assessments. Furthermore, given lecture attendance is low, revisions to timetables should be considered and expanded transportation be made available to students. Lastly, students should be given the necessary time management tools to adjust to greater workloads at university.